Relationship Between Cerebral Hemodynamics, Tissue Oxygen Saturation, and Delirium in Patients With Septic Shock: A Pilot Observational Cohort Study - Qing Feng; Qing Feng; Meilin Ai; Li Huang; Qianyi Peng; Yuhang Ai; Lina Zhang (Frontiers in Medicine, 2021)
Background: Septic shock patients have tendencies toward impairment in cerebral autoregulation and imbalanced cerebral oxygen metabolism. Tissue Oxygen Saturation (StO2) and Transcranial Doppler (TCD) monitoring were undertaken to observe the variations of cerebral hemodynamic indices and cerebral/peripheral StO2 to find risk factors that increase the sepsis-associated delirium (SAD).Materials and Methods: The research cohort was chosen from septic shock patients received in the Department of Critical Care Medicine, Xiangya Hospital, Central South University between May 2018 and March 2019. These patients were separated into two groups, SAD and non-SAD as assessed by using the Confusion Assessment Method for the Intensive Care Unit (CAM-ICU). Comparisons were made between the two groups in terms of peripheral StO2, fluctuations in regional cerebral oxygen saturation (rSO2), cerebral vascular automatic regulation function [Transient Hyperemic Response Ratio (THRR) index], cerebral hemodynamic index, organ function indicators, blood gas analysis indices, and patient characteristics.Results: About 39% of the patients (20/51) suffered from SAD. Nearly 43% of the patients died within 28 days of admission (22/51). Individuals in the SAD cohort needed a longer period of mechanical ventilation [5 (95% CI 2, 6) vs. 1 days (95% CI 1, 4), p = 0.015] and more time in ICU [9 (95% CI 5, 20) vs. 5 days (95% CI 3, 9), p = 0.042]; they also experienced more deaths over the 28-day period (65 vs. 29%, p = 0.011). The multivariate regression analysis indicated that independent variables associated with SAD were THRR index [odds ratio (OR) = 5.770, 95% CI: 1.222–27.255; p = 0.027] and the mean value for rSO2 was < 55% (OR = 3.864, 95% CI: 1.026–14.550; p = 0.046).Conclusion: Independent risk factors for SAD were mean cerebral oxygen saturation below 55% and cerebrovascular dysregulation (THRR < 1.09).